The little crystalline seed : the ontological significance of mise en abyme in post-Heideggerian thought - Dickmann, Iddo, 1972- (Intersections (Albany, N.Y.), 2019)
"Mise en abyme is a term from literary theory denoting a work that doubles itself within itself, for example a story placed within a story or a play within a play. Proliferating in experimental fiction in midcentury France, this technique had a strong impact on contemporary literary theory, but also, as this book project argues, on post-Heideggerian and post-structuralist philosophy. The Little Crystalline Seed focuses on how three of these thinkers invoke the concept of mise en abyme in order to establish ontologies that deviate from that of Heidegger. Iddo Dickmann demonstrates how the concept served in modeling Derrida's logic of supplementarity, Blanchot's philosophy of "ambiguity" and mechanism of Désouvrement, and Deleuze's philosophy of difference, time and repetition. Exploring the interpretative and generative potential of the mise en abyme for continental thought, Dickmann illustrates points of resonance between various philosophical topics such as aesthetics, ethics, time, logic, mirroring, play, and signification"--